Specifics of rural areas of Serbia from the aspects of regional development - Todorović, Marina; Drobnjaković, Marija; Gligić-Simeunović, Anja (Economics of Agriculture, 2010)
The territory of Republic of Serbia is characterized by considerable socio-economic and demographic disproportions, which are result of inadequate legislations of regional development. Regional differences can be ascribed to the relations: north-south, Belgrade agglomeration – the rest of Serbia, centre-periphery, and specially dichotomy between village and city. The consequence of established regional structure led to the neglect of Serbian village, which is experiencing structural changes in spiritual, psychological and technological sphere. Serbian villages represent a traditional undeveloped area. This paper emphasis problems arising from historical neglect of the Serbian village, which primarily concern the rapid abandonment of agriculture and process of deagrarization, and continuing depopulation and demographic erosion of rural areas.